STUDIES OF SAFETY AND FUNCTIONAL AND METABOLIC EFFECTS OF NON-IONIC CONTRAST MEDIA IN CHILDREN WITH NEPHROPATHIES - E.N. Tsygina; I.E. Smirnov; A.G. Kucherenko; G.F. Zadkova; O.F. Lukina; O.O. Kupriyanova; T.E. Sorokina; M.I. Bakanov; S.N. Zorkin; S.P. Yatsyk; A.N. Tsygin (Педиатрическая фармакология)
A study was conducted to assess the safety of non-ionic contrast media in paediatric nephrourology and their impact onto renal function and homeostasis, reflecting the risk of development of contrast-induced nephropathy. After contrast media use we observed elevation of cystatin C and endothelin, decrease of sodium fractional excretion and hypocoagulation were identified. The results obtained indicate that renal hypoperfusion with a consequent decrease of sodium fractional excretion and elevation of endothelin production may play a role in contrast-induced nephropathy. Increased serum cystatin C reflects adverse impact of contrast agents on renal function. Hypocoagulation effect requires that coagulation disorders must be excluded before use of contast media.Key words: children, contrast-induced nephropathy, renal function, cystatin C, endothelin, hemostasis. (Pediatric Pharmacology. – 2010; 7(2):78-82)